2010
DOI: 10.1104/pp.110.168435
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of ATP Synthase and the Cytochrome b  6/f Complexes in Limiting Chloroplast Electron Transport and Determining Photosynthetic Capacity    

Abstract: In C 3 plants, CO 2 assimilation is limited by ribulose 1,5-bisphosphate (RuBP) regeneration rate at high CO 2 . RuBP regeneration rate in turn is determined by either the chloroplast electron transport capacity to generate NADPH and ATP or the activity of Calvin cycle enzymes involved in regeneration of RuBP. Here, transgenic tobacco (Nicotiana tabacum 'W38') expressing an antisense gene directed at the transcript of either the Rieske iron-sulfur protein of the cytochrome (Cyt) b 6 /f complex or the d-subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(118 citation statements)
references
References 44 publications
8
108
0
2
Order By: Relevance
“…In tobacco (Nicotiana spp.) knockdowns of chloroplast ATPase (Rott et al, 2011;Yamori et al, 2011), a decrease in linear electron flow revealed the negative feedback of an excess proton motive force on cytochrome b 6 f activity. In C. reinhardtii, an overacidification of the lumen in DATPase would result in an exaggerated photosynthetic control and be alleviated in DATPase pgr5.…”
Section: Discussionmentioning
confidence: 99%
“…In tobacco (Nicotiana spp.) knockdowns of chloroplast ATPase (Rott et al, 2011;Yamori et al, 2011), a decrease in linear electron flow revealed the negative feedback of an excess proton motive force on cytochrome b 6 f activity. In C. reinhardtii, an overacidification of the lumen in DATPase would result in an exaggerated photosynthetic control and be alleviated in DATPase pgr5.…”
Section: Discussionmentioning
confidence: 99%
“…These searches did not reveal any homologous sequences with more than 18-bp length; therefore, off-target silencing effects of the RNAi construct are unlikely to occur. Furthermore, this sequence is part of the 645-bp-long sequence used to generate the well-characterized tobacco Rieske-2Fe2S antisense plants (Price et al, 1995(Price et al, , 1998Anderson et al, 1997;Yamori et al, 2011).…”
Section: Rnai Plantsmentioning
confidence: 99%
“…It is noteworthy that in investigations published before 1997, cyt-bf contents may have been overestimated by 30%, because the difference extinction coefficient of cytochrome f has been substantially revised since then (Metzger et al, 1997), making a limiting function of the cyt-bf even more likely. A predominant role of the cyt-bf in photosynthetic flux control was ultimately confirmed by the specific inhibition of cyt-bf activity (Kirchhoff et al, 2000) and by an antisense approach against the Rieske protein (Price et al, 1995(Price et al, , 1998Anderson et al, 1997;Yamori et al, 2011).…”
mentioning
confidence: 99%
“…It appeared that the abundance of MCA1 limits the amount of petA mRNA and accordingly levels of the encoded protein, cytochrome f (Raynaud et al, 2007). This and the fact that the activity of the cytochrome b 6 f complex is rate limiting for the light reaction in photosynthesis (Yamori et al, 2011) prompted us to investigate whether PrfB3 also has a regulatory function in petB gene expression. First, we have shown that downregulation of PrfB3 below a threshold of ;25% goes along with a severe reduction in the amount of petB RNA and consequently in the abundance of cytochrome b 6 protein levels ( Figure 8A).…”
Section: Prfb3 Expression Is Highly Responsive To Stress and Environmmentioning
confidence: 99%